Translation techniques and technological tools taken as a resource during the development of a universal language: the translation process - Caballero Trujillo, Karen Lissette
The following report shows the importance of translating at present day since it helps create a universal language so people around the world have the opportunity to share ideas, information or knowledge. Therefore, the translation process is a set of steps the translator has to follow, for translations are not done in a straight line. So, this report provides the basic steps the translators should follow to create professional translations. Furthermore it gives an explanation of the Translation techniques and their significance like: Literal Translation, Borrowing, Calque (loan translation), Modulation, and Adaptation. Finally, it demonstrates how technological tools can be used to translate huge documents like legal and medical documents, pictures with text included, University Transcripts, magazines and comics in a short period of time.